Sosialisasi Tanggap Bencana Alam di Kabupaten Sinjai - Kiki Rasmala Sani; Abd Haris (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This community service was carried out in Pattongko Village, Central Sinjai District, by considering the location's vulnerability to natural disasters such as landslides and tornadoes. The high rainfall in the area is one of the leading causes of frequent natural disasters, compounded by the mountainous and hilly topography. These factors make the community highly susceptible to disasters that result in significant material and immaterial losses. The primary aim of this service activity was to build awareness and strengthen the community's disaster response capabilities, enabling the creation of a disaster-resilient village.The activity was conducted through socialization efforts involving various stakeholders, including the Pattongko village community, the village government, local youth groups, and the Sinjai Regency Regional Disaster Management Agency (BPBD), which served as the lead agency in disaster response in the region. Despite being a one-day event, the activity was expected to provide essential disaster education and training for the local population, enhancing their knowledge of disaster preparedness and response. By doing so, the initiative aimed to minimize the potential victims and the scale of losses caused by natural disasters in the future.This activity also supported broader government programs aimed at forming Disaster Resilient Villages. In the future, the program will be extended with further activities, such as establishing community disaster response teams, organizing disaster simulations, and strengthening disaster management protocols within the village. This long-term plan will ensure that the community remains well-prepared for any potential disaster events